The Effect of Hajj Pilgrimage on Treatment Compliance in Individuals with Chronic Diseases - Yilmaz, Feride Taskin (Journal of religion and health, 2019)
This study was performed in order to determine the effect of Hajj pilgrimage on treatment compliance in individuals with chronic diseases. A total of 168 individuals were included in the prospective and descriptive study. Data were collected in three interviews using a patient identification form and the Religiousness Inclination Scale. When the medicine compliances of the individuals before and after Hajj pilgrimage were compared, a statistically meaningful difference between their regular uses of medicine statuses was found (p = 0.011). However, no difference was detected in the 3-month follow-up (p = 0.094). Additionally, it was found that in individuals with internally driven religiousness inclinations there was no relationship between their statuses regarding having changes in their disease-related complaints after Hajj pilgrimage and their status regarding coping with disease. Hajj pilgrimage was found to negatively affect treatment compliance in the short term in individuals with chronic diseases, while there were no changes in long-term treatment compliance.